Developing Drama Teaching Materials Based on Artificial Intelligence Script Generator for Students of English Literature Department at Universitas Muslim Nusantara Al-Washliyah Academic Year 2024-2025 - Ningsih, Ayu Melati; Risnawaty, Risnawaty; Arfanti, Yulia; Asnawi, Asnawi (IKIP Siliwangi, 2025)
This research is a R & D research aimed at producing drama teaching materials based on AI script generator for use in drama learning for students of the English literature study program UMN al-Washliyah, developing drama teaching materials based on AI script generator to improve students' understanding of writing drama script by using technology, testing the validity and testing the effectiveness of AI based script generators. The result from the research is mean value before using AI script generator-based drama material = 32.5 and mean value after using AI scripts- based drama materials = 42.5 so there is an increase of 10. The validity of the material on the test of the drama material based on AI script generator obtained a 70,5% percentage result with a good category, so it can be concluded that the development of the AI based script material generator deserves and effective to be used in the drama course.